MELATIH PENINGKATAN KETRAMPILAN MENULIS SURAT PRIBADI DALAM BAHASA INGGRIS DENGAN MENGGUNAKAN PADLET PADA SISWA KELAS XI FKK SMK MUHAMMADIYAH 3 PURWOKERO TAHUN PELAJARAN 2020/2021 - Nurhikmah, Ricci Alfera (Jurnal Analisis Pendidikan Sosial, 2025)
English is a foreign language for students in SMK. As we know that the subject matter of English includes four skills, namely: listening, speaking, reading and writing. These four aspects are supported by other language elements, such as: grammatical vocabulary, grammar and pronunciation according to the theme as a means of achieving goals. Writing is one of the language skills that is felt very often to be a problem for students in the process of learning English in class. This can be seen from the results of student learning about the value of the mid-semester assessment (PTS) Odd Semester Class XI FKK SMK MUHAMMADIYAH 3 PURWOKERTO. There are many students still under KKM. The problem attracted the attention of the author in order to try to explain the topic of analysis about the students' ability to write personal letter texts and ask the students to send it via the Padlet link provided. The author has carried out classroom action research and carried out in Class XI FKK with a total of 27 students. On this occasion the goal to be achieved is to improve students' abilities and to increase student creativity in order to compose personal letter texts, develop distance learning strategies and online learning models that are effective, efficient and fun. Students can be actively involved in communication activities with express ideas, opinions and feelings in a simple way both verbally and in writing online. The technique used in this research is to make observations/observations and test student performance in the form of an online written test. From research conducted in September - October 2020. Based on the explanation in the discussion above, the research objectives that have been carried out have been successful. In other words, the implementation of online learning actions using the Padlet link can improve students' ability to write texts in the form of personal letters, it can also increase students' creativity in the online learning process or distance learning and can encourage students to be more open and able to work together again in the process of further learning activities. .